When Offense and Mutual Forgiveness Collide Yearly in Indonesia: A Qualitative Study During Eid al-Fitr - Gunawan, Nanang Erma (Universitas Negeri Yogyakarta, 2020)
One custom of Indonesian Muslims during Eid al-Fitr is to celebrate Ramadhan's end by requesting and giving forgiveness amongst Muslims. This celebration is the symbol of the triumph of the Muslims after a month of fasting and going back to being sinless like a newborn child. While mutual forgiveness has become an adhering religious practice, there is still limited analysis of how individuals deal with themselves about the observed offensive event with other people, and the spiritual practice of forgiving each other. Ten participants who participated in this research to address this issue. To evaluate the gathered data, the researcher conducted a content analysis. Results indicate that pardoning criminals during the Eid al-Fitr can be attainable. Not all the participants could forgive, however, simply because it was during a religious practice. Other causal factors to forgive are the degree of damage, anger, and recognition of the traumatic encounter.